Hospitality and tourism innovation: a systematic literature review - Syafri Naldi; Erna Maulina; Tetty Herawaty; Rusda Irawati (BISMA (Bisnis dan Manajemen), 2022)
Much innovation research focused on the manufacturing sector. Hence, this study aims to fill this gap by focusing on exploring innovation in the tourism and hospitality sector. The study method is a systematic literature review of 40 papers related to the topic. The findings show that hospitality and tourism innovation research has been conducted in different countries and continents, mainly in Europe. The research methods used are mostly quantitative and qualitative. Research respondents are mostly from the supply-side (hotel managers or tourism destination managers). Selected articles have been classified and analysed into three review categories: innovation at the company, regional, and innovation typology in general or macro levels. This study implies radical innovation, network collaborative innovation, service innovation, innovation linked with human resources, hospitality innovation, and technological innovation.